AN EVALUATİON ON THE PLACE OF J. S. MİLL WİTHİN LİBERALİST TRADİTİON (Third Sector Social Economic Review, 2014)
According to Mill, while economic and political power spreads through masses, free market economy based on competition constitutes a paternalist hierarchical structure on labor. Therefore, he lost his absolute trust on laissez – faire economic philosophy. Competition based free market economy of course more superior than feudalism. However, modern industrialized society should produce conditions which might allow institutionalization of individual freedom. Mill is essentially deemed as a representative of classical liberalist tradition. However, he is philosopher who was influenced significantly by socioeconomic developments occurred in eighteenth and nineteenth centuries. Accordingly, he slightly shifted to positive liberalism by addressing liberalism within the framework of moral responsibility. In this context, he is linked to social liberalism which anticipates selective intervention of government to social life and classified as a philosopher who plays a connecting role between classical liberalism and modern liberalism.
Keywords: John Stuart Mill; Economic Freedom; Social Liberalism